Contributing to a self-regulated English language learning process by teacher feedback at an eighth grade at Concejo de Medellin high school (2018)
ABSTRACT: This action research study reports how teacher feedback contributes to a self-regulated learning in an EFL classroom with 8th graders at a public educational institution in Medellín, Colombia. The actions developed were: choosing a topic to work with, dividing students into groups, developing activities connected to students’ realities, giving feedback and having self and peer-assessment at specific moments, and evaluating the final results of project work. Data collection techniques included teacher’s journal, two surveys to students, and an interview to the CT. Findings revealed that working by projects students were more autonomous and responsible, and also became aware that they needed to take decisions to make progress in the English course. Teacher feedback was part of the process that allowed students to self-regulate their learning, because they learnt about their strengths and weaknesses and how to overcome difficult learning situations.